Identification of the Anthelmintic Power of Anting-anting Leaf and Starfruit Leaf - Sri Sulami Endah Astuti (Health Notions, 2020)
Ascariasis is an intestinal infection caused by the parasitic worm Ascaris lumbricoides. Starfruit leaf (Averrhoa bilimbi) and leaf anting-anting (Acalypha indica L) is a plant that is often used as a worm remedy in the community. Starfruit leaves (Averrhoa bilimbi) and Leaf anting-anting (Acalypha indica L) contain several compounds that have the potential as anthelmintics, namely saponins, tannins and flavonoids. The purpose of this study was to determine the effect of ethanol extention of starfruit leaf leaves (Averrhoa bilimbi) and leaf anting-anting (Acalypha indica L) as anthelmintic on the time of death of Ascaris suum Goeze worms in vitro. The method in this study is experimental with post test only group design. Test animals from the study are Ascaris suum. The study was conducted at the Parasitology Laboratory, Medical Laboratory Department, Poltekkes Kemenkes Surabaya in 2019. This study used 6 treatment groups, NaCl 0.9% as a negative control and pirantel pamoate 0.25% as a positive control and ethanol extract of wuluh starfruit leaf and ethanol extract of Anting-anting with concentrations of leaves. 40%, 60%, 80% and 100%. Data were analyzed using the Kolmogrov-Smirnov test, the Anova two way Block Design test, then continued using the Post Hoc test to determine differences between blocks and between treatments, against the time of Ascaris suum worm's death. The average time of death of Ascaris suum caused by ethanol extract of starfruit leaves concentration of 40% for 492.3 minutes and ethanol extract of leaf anting-anting 396.5 minutes, concentration of 60% ethanol extract of wuluh starfruit leaves for 278.5 minutes and leaf extract ethanol leaf anting-anting for 283.5 minutes, 80% concentration of ethanol extract of wuluh starfruit leaf for 141.8 minutes and ethanol extract of anting-anting leaf for 174 minutes, 100% concentration of ethanol extract of wuluh starfruit leaves for 66.75 minutes and extract ethanol leaf anting-anting for 92 minutes. So it can be concluded that the ethanol extract of starfruit leaves has an anthelmintic effect on the Ascaris suum worm more optimum than the ethanol extract of the Anting-anting leaves, because the time required is close to positive control that is 60 minutes. Keywords: anthelmintic; Ascaris suum; starfruit leaf; anting-anting leaf